COMPREHENSIVE REVIEW ON THE ETHICAL AND LEGAL IMPLICATIONS OF ARTIFICIAL INTELLIGENCE IN HEALTH CARE. - Abdullah Salem Hamad Al Sulaiman, ‏Hadi Mazyad.M Albahri, ‏Mohammed Saleh Bin Mohammed AlKhamsan, ‏Hussain Mohammed Hamad AL sulaiman, ‏Mohsen Mana HutaylanAlmuhmidhi, ‏Al yami, Hamad Mana (Chelonian Research Foundation, 2023)
Integrating artificial intelligence (AI) innovation into healthcare frameworks guarantees to be helpful but, moreover, poses moral and lawful challenges. This survey investigates critical issues in AI selection in healthcare, cantering on moral and legitimate issues. Protection is becoming a significant issue, including the security of understanding data and the potential disintegration of protection in AI-enabled frameworks. Moreover, the investigation investigates the effect of algorithmic predisposition, highlighting the significance of fairness and straightforwardness within the decision-making process. Accountability is critical, highlighting the need to clarify parts and duties in AI-based healthcare. Administration issues emerge, and existing frameworks must keep up with fast, innovative improvements. Thoughts to fathom these issues incorporate reinforcing information assurance, making the method straightforward, and empowering collaboration. By tending to moral and legitimate issues, partners can use the transformative potential of artificial intelligence while guaranteeing quiet rights, equity, and the security of treatment. Keywords: artificial intelligence, healthcare, ethics, legal implications, privacy, bias, accountability, regulatory challenges